2015
DOI: 10.1039/c4tb01873g
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the hydrophilic–lipophilic environment on the structure of silk fibroin protein

Abstract: The present study examines the influence of the hydrophilic-lipophilic environment, mediated by small molecules, on the structural changes in silk protein fibroin. Small molecules mediate the various hydrophilic-lipophilic balances (HLBs) that impact the organisation of silk protein chains. Changes in the silk fibroin structure due to additives are related to the HLB value. At HLB > 10, silk fibroin primarily forms Silk I crystalline structures. Small molecules with HLB < 8.9 primarily induce the formation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
40
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 33 publications
(47 reference statements)
4
40
1
Order By: Relevance
“…The peak at 24.2° is attributed to the less ordered crystalline form of β‐sheet structures, with crystalline spacing of 3.7 Å . The diffraction profile of the SFOP foam also shows weak peaks at angles 12.2° and 19.7° (crystalline spacing of 7.4 and 4.5 Å), which are also associated to the less ordered β‐sheet crystalline form . This can be attributed to the presence of the OP filler, which influences the self‐assembly into β‐sheet crystallites during the protein gelation, causing an increase of the less ordered content.…”
Section: Resultssupporting
confidence: 64%
See 2 more Smart Citations
“…The peak at 24.2° is attributed to the less ordered crystalline form of β‐sheet structures, with crystalline spacing of 3.7 Å . The diffraction profile of the SFOP foam also shows weak peaks at angles 12.2° and 19.7° (crystalline spacing of 7.4 and 4.5 Å), which are also associated to the less ordered β‐sheet crystalline form . This can be attributed to the presence of the OP filler, which influences the self‐assembly into β‐sheet crystallites during the protein gelation, causing an increase of the less ordered content.…”
Section: Resultssupporting
confidence: 64%
“…As shown in Figure c, both samples exhibit a prevalent highly ordered structure. The most intense peak at 20.6° is typical of the highly ordered crystalline form characterized by the intra‐hydrogen‐bonded β‐sheet structure, which corresponds to a crystalline spacing of 4.3 Å . The peak at 24.2° is attributed to the less ordered crystalline form of β‐sheet structures, with crystalline spacing of 3.7 Å .…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Additives such as polyalcohols impact the SF structure to a variable extent depending on their hydrophilic–lipophilic balance (HLB) value. Lu et al . recently demonstrated that upon addition of polyalcohols with HLB>10, SF primarily exists as silk I.…”
Section: Resultsmentioning
confidence: 99%
“…Pure SF (Figure a) presented absorption bands at 1647 cm −1 and 1545 cm −1 that corresponded to amide ‐ I (C = O stretching) and amide ‐ II (N‐H bending) of silk II structural conformation (β‐sheet). Another absorption band observed at 1247 cm −1 corresponded to amide ‐ III (C‐N stretching), which is typically silk I conformation (α‐helix or random coil structure) . Peaks were observed at 1411 cm −1 (due to symmetric stretching vibrations of carboxylate group) and 1339 cm −1 (indicating the presence of methylic groups of alanine in the silk chain).…”
Section: Resultsmentioning
confidence: 99%